Drink Less Enjoy More: effects of a multi‐component intervention on improving adherence to, and knowledge of, alcohol legislation in a UK nightlife setting. (23rd April 2018) - Quigg, Zara; Hughes, Karen; Butler, Nadia; Ford, Kat; Canning, Ian; Bellis, Mark A.
Abstract: Aims: To estimate the association between implementation of a community‐based multi‐component intervention (Drink Less Enjoy More) and sales of alcohol to pseudo‐intoxicated patrons and nightlife patron awareness of associated legislation. Design: Cross‐sectional pre‐intervention and follow‐up measurements, including alcohol test purchases (using pseudo‐intoxicated patrons) in licensed premises (stratified random sample; 2013, 2015) and a survey with nightlife patrons (convenience sample; 2014, 2015). Setting: One UK municipality with a large night‐time economy. Participants: Licensed premises (pre = 73; follow‐up = 100); nightlife patrons (pre = 214; follow‐up = 202). Intervention: The Drink Less Enjoy More intervention included three interacting components: community mobilization and awareness‐raising; responsible bar server training; and active law enforcement of existing legislation prohibiting sales of alcohol to, and purchasing of alcohol for, a person who appears to be alcohol intoxicated: 'intoxicated', herein for economy. Measurements: The primary outcomes were alcohol service refusal to pseudo‐intoxicated patrons and nightlife patron knowledge of alcohol legislation (illegal to sell alcohol to, and purchase alcohol for, intoxicated people), adjusted for potential confounders including characteristics of the area, venue, test purchase and nightlife patron. Findings: Pre‐intervention, 16.4% of alcohol sales were refused, compared with 74.0% at follow‐up ( P  < 0.001). In adjusted analyses, the odds of service refusal were higher at follow‐up [adjusted odds ratio (aOR) = 14.63, P  < 0.001]. Service refusal was also associated with server gender and patron drunkenness within the venue. Among drinkers, accurate awareness of alcohol legislation was higher at follow‐up (sales: pre = 44.5%; follow‐up = 66.0%; P  < 0.001/purchase: pre = 32.5%; follow‐up = 56.0%; P  < 0.001). In adjusted analyses, knowledge of legislation was higher at follow‐up (sales: aOR = 2.73, P  < 0.001; purchasing: aOR = 2.73, P  < 0.001). Knowledge of legislation was also associated with participant age (purchasing) and expectations of intoxication (sales). Conclusion: A community‐based multi‐component intervention concerning alcohol sales legislation in the United Kingdom (UK) was associated with a reduction in sales of alcohol to pseudo‐intoxicated patrons in on‐licensed premises in a UK nightlife setting and an improvement in nightlife patron awareness of associated legislation.